59.3k views
13 votes
4(x + 3) = 3(3x -1) solve for x

User Boyo
by
5.0k points

2 Answers

6 votes

Answer:

x = 3

Explanation:

start off by distributing

4(x +3) turns into 4x + 12

3(3x - 1) turns into 9x - 3

so your equation turns into

3x + 12 = 9x - 3

then you can subtract the x values to move it to the opposite side of the equal sign (=)

3x + 12 = 9x - 3

-3x -3x

----------------------

12 = 3x - 3

then add the -3

(to find out how to move the values to opposite sides of the equals sign, just isolate the number. whether it is - 3 or just 7x, you keep the sign in front of it. if it is multiplying then divide it to get rid of it. make sure to do it to both sides of the equation.)

12 = 3x - 3

+3 +3

----------------

15 = 3x

divide 3 on both sides

15/ 3 = 3

3x/3 = x

3 = x

the value of x is 3

hope this helps:)

User Weved
by
4.6k points
6 votes

Answer:

x = 3

Explanation:

4(x + 3) = 3(3x - 1) ← distribute parenthesis on both sides

4x + 12 = 9x - 3 ( subtract 9x from both sides )

- 5x + 12 = - 3 ( subtract 12 from both sides )

- 5x = - 15 ( divide both sides by - 5 )

x = 3

User Pavel Alazankin
by
4.7k points